CrossCultural Leadership in Higher Education: An Analysis of University Leaders' Perspectives - Anik Safitri; Achmad Fany Fandholi; Muhammad Ziqi Qolbi (International Journal of Studies in International Education, 2024)
The study investigates the perspectives of university leaders from diverse cultural backgrounds on crosscultural leadership in higher education. Through indepth interviews, this research uncovers how leaders perceive and address cultural diversity, communication barriers, and ethical considerations in their roles. Findings suggest that leaders who prioritize cultural empathy and open communication are more effective in fostering inclusive educational environments. This paper provides a framework for crosscultural leadership training and policy recommendations.